Застосування теорії балок для побудови плоских двічі диференційованих замкнутих кривих за неточними дискретними даними - Orynyak, Igor; Koltsov, Dmytro; Chertov, Oleg; Mazuryk, Roman (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2022)
The smoothing of measured noisy positions of discrete points has considerable significance in various industries and computer graphic applications. The idea of work consists of the employment of the technique of beam with spring supports. The local coordinates systems are established for beam straight line segments, where the initial angles between them are accounted for in the conjugation equations, which provide the angular continuity. The notions of imaginary points are introduced, the purpose of which is to approach the real length of the smoothed contour to the length of the straight chord. Several examples of closed denoised curve reconstruction from an unstructured and highly noisy 2D point cloud are presented.